Pengaruh Lingkungan Kerja Fisik, Komitmen Organisasi dan Work Life Balance terhadap Kinerja Karyawan - Swasti, Ni Luh Putu Raka Surya; Hartati, Putu Sri; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study was to analyze the effect of the physical work environment, organizational commitment and work life balance on employee performance at PT. Dharma Bhakti Mukti. Determination of the sample in this study with saturated sampling technique. The sample in this study were all employees of PT. Dharma Bhakti Murti with 42 employees. Data collection was carried out by observation, interviews, questionnaires and documentation. The results of the analysis found that the physical work environment, organizational commitment and work life balance partially and simultaneously have a positive and significant effect on employee performance at PT. Dharma Bhakti Murti. Suggestions in this study are that the leadership of PT. Dharma Bhakti Mukti to further improve the cleanliness of the work environment so as to provide comfort for employees at work, leaders should provide work motivation to employees so that employees will survive and have a high level of loyalty, leaders provide work schedules and appropriate holidays/rest for employees so that employees are able balance work time with family time.